Pengaruh Kompetensi Teknis Dan Komitmen Organisasi Terhadap Kerja Guru Dimediasi Efikasi Diri Pada Madrasah Aliyah Madani Alauddin Kabupaten Gowa - Tacong, Samrawati; Echdar, Saban; St. Hatidja (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2026)
Purpose – This study aims to analyze the role of technical competence and organizational commitment in enhancing teacher performance through the mediating role of self efficacy within the context of sustainable Sharia educational management.. Method – This study employs a quantitative approach using a saturated sampling technique involving 105 teachers at Madrasah Aliyah Madani Alauddin, Gowa Regency, Indonesia. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS). The analysis evaluates both direct and indirect relationships among the variables. Findings – The findings indicate that technical competence and organizational commitment significantly influence teacher performance both directly and indirectly through self efficacy. Technical competence significantly strengthens teachers’ confidence in performing instructional tasks, while organizational commitment fosters psychological attachment and responsibility toward institutional goals. Self efficacy plays a mediating role by strengthening the impact of both competence and organizational commitment on teacher performance.. Implication – These findings highlight the importance of integrating professional competence development, organizational commitment, and psychological empowerment in building sustainable Sharia educational management. Strengthening these dimensions contributes to improving teacher professionalism and sustaining the performance of Islamic educational institutions.